Trends in the incidence of rain rates associated with outages on fixed links operating above 10 GHz in the southern United Kingdom - Paulson, Kevin S. (Radio science, 2010)
Studies have shown that climate change is leading to an increase in the incidence of heavy rain in the United Kingdom, particularly over winter. The major interest has been on the hydrological impacts of this increase, and so studies have focused on rain accumulations over hours or days and for large catchments. The availability of fixed, microwave links is limited by the incidence of heavy rain with an integration time of a minute or less. This document introduces evidence of an increasing trend in rain rates associated with outages. High-resolution rain data, produced by 30 tipping bucket gauges sited in the south of England, have been analyzed to identify these trends. The data span up to 20 years at each site. Increasing trends in the incidence of rain rates exceeded at annual time percentages between 0.005% and 0.1% are demonstrated. Data suggest that the total annual outage would have doubled or tripled over each decade analyzed for the majority of fixed links operating at rain fade limited frequencies. It is plausible that this trend could continue.
Keywords: Electrical and Electronic Engineering; General Earth and Planetary Sciences; Condensed Matter Physics